REFORMASI KEBIJAKAN PERDAGANGAN INTERNASIONAL DAN DEKOMPOSISI PERTUMBUHAN TOTAL FACTOR PRODUCTIVITY (TFP) PADA INDUSTRI TEKSTIL (ISIC 32) DAN INDUSTRI KIMIA (ISIC 35) INDONESIA: ANALISIS INDEKS FÃ„REPRIMONT - Bernadetta Dwi Suatmi (Jurnal Manajemen, 2020)
Theoretically, trade reform is believed to have positive effects on TFP (total factor productivity) in the manufacturing sector. However, empirical studies show mixed evidence about the effect of trade reform on TFP in the manufacturing sector. The objective of this research is to calculate and decompose TFP growth in Indonesian textile (ISIC 32) and chemical (ISIC 35) industries from 1981 to 2000. TFP is calculated and decomposed using the FÃ¤re-Primont index according to sub-periods of trade reform. Results show that at two-digit level, both of textile and chemical industry, TFP growth is positive over the period 1981 to 2000. The main difference between the two sectors is on the main driver of TFP growth. While in the textile industry the main driver of TFP growth is technical progress, in the chemical industry the main driver of TFP growth is technical efficiency. In addition, the analysis of TFP growth and its components at the five-digit level of the textile industry and the three-digit level in the chemical industry show that TFP growth and its components vary across sub-sectors and sub-periods. Based on these results, it is better for the government to formulate the policy of international trade reform based on the industry's characteristics. Keywords: Total Factor Productivity, Index Fare-Primont